Vitamins and Minerals on the Health of Human Body According to Perspective of the Quran - Santika, Pebby Udi; Mareza, Yana; Hasanah, Qomariah (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Vitamins are organic compounds of carbon, hydrogen, oxygen, and sometimes nitrogen that is required in small amounts for normal metabolism, growth, and development. Vitamins and minerals have a very big influence on the human body so that humans can live properly and know the health of their bodies. Fat-soluble vitamins consist of vitamins A, D, E and K. Water-soluble vitamins consist of B complex vitamins and vitamin C. Humans really need different minerals like organic minerals, inorganic minerals, macrominerals, and microminerals. The purpose of this journal article is to find out that vitamins and minerals are related to the Qur’an. This study uses a qualitative approach through a review of vitamin and mineral literature from the perspective of the Koran. Sources of research information come from books, Al-Quran, documents and magazines. The purpose of this article is to make it easier for readers to relate the two as found in QS Yunus verse 24, QS Al-Mu’minun verse 19, and QS Al-Waqiah verse 68 regarding the content of vitamins and minerals.